ANTIBACTERIAL ACTIVITY OF ETHANOL EXTRACT OF KERSEN LEAF (Muntingia calabura L.) TOWARDS Escherichia coli BACTERIA - Sri Marfuati; Mustika Weni; Emilia Putri Agustin (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Escherichia coli is a bacteria that causes infection. In Indonesia, it has been reported that Escherichia coli is resistant to several types of antibiotics; therefore, other alternatives are needed to inhibit the growth of this Escherichia coli. One alternative method is to use medicinal plants, such as cherry leaves, which contain flavonoids, saponins, and tannins as antibacterials. Aim to determine the antibacterial activity of an ethanol extract of cherry leaves (Muntingia calabura L.) against Escherichia coli bacteria. The research used a post-test-only control group design. This study contained 7 groups: 1 positive control group, 1 negative control group, and 5 treatment groups. The treatment group consisted of an ethanol extract of cherry leaves with concentrations of 1%, 2%, 4%, 8%, and 10%. The control group was a positive control (K(+) with co-trimoxazole and a negative control (K(-) namely dimethyl sulfoxide (DMSO) at 10%. The data used was One-way ANOVA. The results of this study were the average zone of inhibition. The largest is at a concentration of 10%, namely 6 mm, while the smallest average inhibition zone is at a concentration of 4%, namely 4.37 mm. Concentrations of 2% and 1% do not indicate the presence of an inhibition zone. From these results it is concluded that there are significant differences between The concentration of cherry leaf ethanol extract against Escherichia coli bacteria and the minimum inhibitory level of cherry leaf ethanol extract against Escherichia coli bacteria is at a concentration of 4% with an average inhibition zone of 4.37mm.